"Rejang Ilud, the Sacred Dance of Empowerment and Symbolism" - Suratmaja, Dewa Dwi Ardi (Bali Tourism Journal, 2023)
Bali is known for having numerous centers of classical art, but since the 1970s, the artistic focal point of the island has been Gianyar Regency. The 1970s marked Bali's shift toward culture-based tourism, making tourists more aware of the rich artistic heritage in Gianyar. The sacred Rejang Ilud dance, which accompanied Hindu ceremonies, was once prevalent in this village. However, over the past 15 years, it has been supplanted by the Rejang Dewa dance, a common occurrence with Rejang dances across Bali. Rejang Ilud dance represents a synthesis of various communication elements, including movement as the dance choreography, sound and language as the accompanying music, and appearance as the makeup and costume—a reality shaped by complementary forms. The understanding of the diverse communication elements found in dance goes beyond rational comprehension; the sharpness of perception is vital in capturing the true essence. Recently recognized by the government as a National Intangible Cultural Heritage (WBTB) in 2021, the Rejang Ilud Dance in the village of Buahan, Payangan District, Gianyar, features a distinctive move called Ngilud. This motion involves the palm seemingly grasping something and moving from the inside to the outside. The presence of the ngilud movement can be associated with bodhyagiri mudr?, a hand gesture symbolizing the act of grasping. The awareness of women regarding their role can potentially impede or rectify the hastening of the era of destruction (kaliyuga). Hinduism itself teaches that the destruction of the world is significantly influenced by the Sakti community.